Pengaruh sistem perpajakan dan kepatuhan perpajakan terhadap persepsi wajib pajak mengenai etika penggelapan pajak - Hani, Isma (Maliki Interdisciplinary Journal, 2024)
Taxes are one of the means of payment when there is government spending and are an important component of a government's revenue. A good self-assessment tax system has the potential to reduce taxpayer perceptions regarding the ethics of tax evasion, because a good system will make it easier for taxpayers to carry out their obligations. Tax policy is about the high and low tax rates, the structure of the tax system, and the accountability of tax contributions needed to fund government operations and development. If self-assessment is implemented properly, it will have an impact on the optimization of taxation and ensure taxpayer compliance to consistently pay their taxes so that it will reduce the tendency of tax evasion. Tax evasion will occur when the government requires taxpayers to fulfill their taxes. Tax evasion is caused because the perspective on taxes is different from the government's way of thinking.